Nonlinear dynamic analysis of aquaculture platforms in irregular waves based on Hilbert–Huang​ transform. (February 2023) - Ma, Chao; Xie, Sida; Bi, Chun-Wei; Zhao, Yun-Peng
Abstract: This study aimed to examine the nonlinear dynamics of aquaculture platforms using the Hilbert–Huang transform (HHT). First, a numerical model that couples the boundary element method and lumped-mass model was used to simulate the dynamic behavior of a multi-body floating aquaculture platform in irregular waves. Second, a time–frequency analysis method based on the HHT was used to analyze the dynamic responses, including motion and mooring force responses. The results highlight that the surge motion of the net cage is dominated by the low-frequency components, whereas the heave and pitch motions are dominated by the wave-frequency components. The pitch response of the net cage has an obvious energy concentration near the peak frequency region of the incident wave. The surge motion of the net cage in the middle of the platform has a greater response to wave components with lower frequencies than that of the other two cages. The inherent characteristic vibration form of the mooring force response is affected by both the low-frequency characteristic of surge motion and the wave-frequency characteristic of motions in the vertical plane. The amplitudes of the wave-frequency components of the mooring force are much larger than those of the low-frequency components, which is like the characteristics of heave and pitch motions. The gravity periods of the wave-frequency mode components of the mooring force response were very close to the gravity period of the surge motion.